ANALISIS YURIDIS PENDAFTARAN PERKAWINAN BAGI WARGA NEGARA INDONESIA YANG MELANGSUNGKAN PERKAWINAN DENGAN WARGA NEGARA ASING BERDASARKAN SISTEM ADMINISTRASI KEPENDUDUKAN DI INDONESIA - Totok Arianto (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
Legal developments can be seen from the legal activities of Indonesian citizens who come into contact with foreign nationals, such as marriages between Indonesian citizens and foreign nationals abroad. In Law Number 1 of 1974 Concerning Marriage Article 2 Paragraph 2 states that every marriage is recorded according to the applicable laws and regulations. What if the country where Indonesian Citizens and Foreign Citizens who are married do not organize marriages, therefore there are other laws that regulate matters related to marriage registration, namely the Population Administration Law. The type of research used is normative juridical, namely this type of research focused on examining the application of the rules or norms in positive law. Called by the term library research. It is called library research because in normative legal research it is carried out by examining library materials or secondary data only, the conclusion from this research is that marriages abroad carried out by Indonesian citizens with foreign nationals must be registered with the competent authority in the country. locally and reported to the representative of the Republic of Indonesia. If the country where the marriage is held does not organize marriage registration for foreign nationals, the marriage registration can be done at the local representative of the Republic of Indonesia and must be registered when they arrive in Indonesia. husband and wife.